Study of the Regularities of Higher Nervous Activity Impairments in the Posttraumatic Period - T. F. Sokolova; A. S. Khizhnyak; N. Ye. Turok; S. S. Stepanov; V. V. Semchenko (Общая реаниматология, 2006)
The regularities of higher nervous activity impairments were studied in an experiment on mature albino rats in the posttraumatic period, by using the open field test. Analysis of behavioral acts indicated the difficulties encountered in constructing an adequate response to get a benefit from an activity (danger avoidance) at stages of traumatic disease due to the impossibility of rapidly and accurately solving the intricate problems facing the damaged brain. At the same time, a great contribution to higher nervous activity impairments was made by emotional disorders that were traced up to the end of a follow-up (on day 30). The found changes in higher nervous activity are indicative of the high plasticity of the central nervous system and its great capabilities to perform compensatory and adaptive processes under extreme conditions, by reorganizing the intricate system of links of its individual parameters.